STRATEGI PEMBELAJARAN TAHSIN DAN TAHFIZH SERTA IMPLIKASINYA TERHADAP KUALITAS BACAAN DAN HAFALAN - Nadia Humaira; Pahrurroji; Muh. Ubaidillah Al-Ghifary Slamet (Qiro'ah : Jurnal Pendidikan Agama Islam, 2023)
This research aims to analyze Tahsin and Tahfizh learning strategies, reveal the implications of using these strategies, and reveal future development plans for Tahsin and Tahfizh learning. This research uses a qualitative approach, a type of field research sourced from primary and secondary data. Data collection techniques through observation, interviews, documentation. The research results are 1). There are 3 learning strategies for Tahsin and Tahfizh MAN 1 HSU, namely planning, implementation and evaluation, 2). The implications of using this strategy are that teachers deepen their knowledge of the Qur'an, repeat memorization, reduce students' difficulties, students have good morals, understand the contents of the verses, are disciplined, hardworking, patient, independent, honest, grades meet targets, achieve well, become the school of choice , a school atmosphere that loves the Koran, parents learn Tahsin, alumni become donors and 3). Future plans for developing Tahsin and Tahfizh learning include teacher training, making it a special class, making certificates, graduation, acceleration, allocating funds, freeing tuition fees, facilitating students to go to university, requirements for taking diplomas, and cooperation with Tahfizh institutions.